Viadukt Pesnica – inovacije v železniški infrastrukturi - Markelj, Viktor (Gradbeni vestnik, 2023)
The article describes the Pesnica railway viaduct – from concept, analysis, construction to service. The 912.60-metre-long doubletrack viaduct is the longest railway viaduct in Slovenia. A slab track, featuring a continuous welded rail without track expansion joints, is laid over it. The viaduct is designed as a reinforced concrete prestressed integral structure, consisting of 32 spans, each with an average length of 28 m. In addition to its interesting history, the new viaduct also boasts with an innovative technical design conceived as an integral structure without structural bearings. Each of the 112 m long frame segments is connected by split columns, facilitating mutual dilatation of the frames. The article also describes the analysis of the viaduct with specific features and the load test at the end.
Keywords: analiza; analysis; integral structure; integralna konstrukcija; prednapeti beton; pre-stressed concrete; railway viaduct; slab track; tir na togi podlagi; železniški viadukt